Protease activity in extracellular products secreted in vitro by trophozoites of Giardia duodenalis - de Carvalho, Thais Batista [UNESP]; David, Erica Boarato [UNESP]; Coradi, Silvana Torossian; Guimaraes, Semiramis [UNESP] (Springer, 2008)
There are evidences that Giardia trophozoites contain and/or release proteolytic enzymes that may be implicated in pathogenesis of giardiasis. This report describes a preliminary characterization of the proteolytic activity in excretory/secretory (E/S) products of Giardia duodenalis trophozoites of an axenic Brazilian strain (BTU-11) and the reference strain Portland 1 (P1). The protease activity of E/S products in conditioned medium by trophozoites of each strain was analyzed using substrate (gelatin and collagen) impregnated SDS-PAGE and hemoglobin assay. The protease characterization was based on inhibition assays including synthetic inhibitors. Proteolytic products were detected in the conditioned medium by trophozoites of both assayed strains. In the gels containing copolymerized gelatin and collagen, E/S products promoted degradation of the substrates and the most evident proteolysis zones were distributed in the migration regions of 77 to 18 kDa and 145 to 18 kDa, respectively, in the patterns of gelatinolytic and collagenolytic activities. Degradation of hemoglobin was also observed, and the pattern of hydrolysis was similar in both E/S products assayed. Inhibition assays showed that the main proteolytic activity in both E/S products is due to cysteine proteases although the presence of serine proteases was also indicated, mainly in the hydrolysis of hemoglobin.